Comparison of Retinal Layer Thicknesses of Highly Myopic Eyes and Normal Eyes - Kim, Tae Yeon (Korean J Ophthalmol, 2020)
PURPOSE: To evaluate the differences in individual segmental retinal layer thickness in adult patients with high myopia. METHODS: This study compared the retinal layers of patients with high myopia (axial length of ≥26.0 mm) with those of normal controls using spectral-domain optical coherence tomography. The thicknesses of the retinal layers were compared using nine Early Treatment Diabetic Retinopathy Study subfields. Choroidal thickness was also measured in the subfoveal area. RESULTS: We included 37 eyes with high myopia and 37 eyes of healthy subjects. The mean age was 42.95 and 47.73 years (p = 0.114), and the mean axial length was 27.28 and 24.47 mm (p < 0.001), respectively. The parafoveal areas (outer ring segment) of the ganglion cell layer and inner plexiform layer, all segmental areas except the subfoveal region of the inner nuclear layer, most segmental areas (inner superior, inner inferior, outer superior, outer temporal, and outer nasal) of outer plexiform layer, and most segmental areas (subfovea, inner temporal, inner inferior, inner nasal, outer temporal, and outer inferior) of outer nuclear layer were thinner in eyes with high myopia than in normal eyes (all p < 0.05). There were no statistically significant differences between the levels of photoreceptor layer, retinal pigment epithelium, and nerve fiber layer. The mean choroidal thickness was 153.81 ± 64.80 and 239.54 ± 44.28 μm in the high myopia and control groups, respectively, which were significantly different (p < 0.001). CONCLUSIONS: In high myopia without pathologic changes, there was a meaningful thinning of the retina and choroid, especially in most Early Treatment Diabetic Retinopathy Study subfield areas of the deep vascular complex, perifoveal area of the superficial vascular complex, and most areas of the outer nuclear layer in the outer retinal layer, which are associated with myopic axial elongation.